Perbandingan Di Antara Pengarah Lelaki Dan wanita Dalam Elemen Ferninisme - Wan Zainab, Che Seman (Universiti Malaysia Sarawak, (UNIMAS), 2016)
Researcher wan to identify the tendency of women and men directors in terms of feminism application. Researcher would like to analyze the cognitive and psychological factors among men and women directors which one has tend to put the elements of feminism. Conducting this research in interview and qulitative tools because it will projects subjective data. Researcher foundout that the tendency of directory was very subjective because they also have to comply with the producer and commercial value